Vascular histopathology and connective tissue ultrastructure in spontaneous coronary artery dissection: pathophysiological and clinical implications. Issue 7 (28th May 2021) - Margaritis, Marios; Saini, Francesca; Baranowska-Clarke, Ania A; Parsons, Sarah; Vink, Aryan; Budgeon, Charley; Allcock, Natalie; Wagner, Bart E; Samani, Nilesh J; von der Thüsen, Jan; Robertus, Jan Lukas; Sheppard, Mary N; et al.
Abstract: Aims : Spontaneous coronary artery dissection (SCAD) is a cause of acute coronary syndromes and in rare cases sudden cardiac death (SCD). Connective tissue abnormalities, coronary inflammation, increased coronary vasa vasorum (VV) density, and coronary fibromuscular dysplasia have all been implicated in the pathophysiology of SCAD but have not previously been systematically assessed. We designed a study to investigate the coronary histological and dermal collagen ultrastructural findings in SCAD. Methods and results: Thirty-six autopsy SCAD cases were compared with 359 SCAD survivors. Coronary and myocardial histology and immunohistochemistry were undertaken. Transmission electron microscopy (TEM) of dermal extracellular matrix (ECM) components of n = 31 SCAD survivors and n = 16 healthy volunteers were compared. Autopsy cases were more likely male (19% vs. 5%; P = 0.0004) with greater proximal left coronary involvement (56% vs. 18%; P < 0.0001) compared to SCAD survivors. N = 24 (66%) of cases showed no myocardial infarction on macro- or microscopic examination consistent with arrhythmogenic death. There was significantly ( P < 0.001) higher inflammation in cases with delayed-onset death vs. sudden death and significantly more inflammation surrounding the dissected vs. non-dissected vessel segments. N = 17 (47%) cases showed limited intimal fibro-elastic thickening but no features of fibromuscular dysplasia and no endothelial or internal elastic lamina abnormalities. There were no differences in VV density between SCAD and control cases. TEM revealed no general ultrastructural differences in ECM components or markers of fibroblast metabolic activity. Conclusions : Assessment of SCD requires careful exclusion of SCAD, particularly in cases without myocardial necrosis. Peri-coronary inflammation in SCAD is distinct from vasculitides and likely a reaction to, rather than a cause for SCAD. Coronary fibromuscular dysplasia or increased VV density does not appear pathophysiologically important. Dermal connective tissue changes are not common in SCAD survivors. Graphical Abstract: